Technikwenden | Technological Turns Historische Perspektiven auf soziotechnische Um- und Aufbrüche | Historical Perspectives on Sociotechnical Transitions - Weber, Heike (Nomos Verlagsgesellschaft mbH & Co. KG, 2023)
Narratives of technology-related transformations or, in German discourse, of 'turnarounds', such as the 'Energiewende', are currently experiencing a heyday. In particular, scenarios of a post-fossil fuel transfor-mation frame technology as the key to mastering the path to a climate-neutral society. This book aims to examine these current challenges from a historical perspective. Its contributions historicise the idea of a technology-driven 'turnaround'. They analyse past socio-technical transitions in the fields of energy, transport, the circular economy and digitalisation, as well as in crisis-induced upheavals. They discuss to what extent these changes can serve as 'usable pasts' to expand or correct our current thinking about and hopes for technological change. With contributions by Christian Hen